(untitled) (Journal of Analytical Oncology, 2012)
In various situations, in clinical practice or for prevention purposes directed at skin cancer, a broadened use of phototesting to estimate individual skin UV-sensitivity may be warranted. The aim of the present study was to investigate, in a primary health care population, the reliability of patient performed reading of a UVB phototest, when compared to the reading of a trained physician. Thirty-two subjects, all patients recruited in a primary health care population, underwent a UVB phototest, applied on the forearm. Test reading was performed after 24 hours, by the subjects themselves, by counting the number of erythemal reactions (0-6) detectable, and immediately after this, an independent control reading performed by a doctor was also done. The results showed a 72% absolute agreement between the subjects’ readings and the control readings, and with a weighted kappa-value of 0.78 (95 CI: 0.64 - 0.91), i.e. corresponding to "substantial agreement". In conclusion, patient performed self-reading of a UVB phototest appears to be a fairly reliable method for estimation of individual skin UV-sensitivity, when compared to the reading of a trained observer. The finding opens up for a broadened use of phototesting in clinical practice and for preventive initiatives aiming at identifying at-risk individuals and reducing sun exposure.